2019
DOI: 10.1177/0958305x19882382
|View full text |Cite
|
Sign up to set email alerts
|

The influence of democracy on emissions and energy efficiency in America: New evidence from quantile regression analysis

Abstract: This study explores whether the development of democracy can significantly affect CO2 emissions and the energy efficiencies in the countries. Database reference from Freedom House, Polity IV project and World Development Indicator was applied to analyze the relationship between the democracy development, CO2 emissions and the energy efficiency of 26 countries in America from the year 1990 to 2013. Empirical result shows that the deepening democracy has a significant impact on the reduction of national CO2 emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Based on the parametric frontier approach of energy efficiency performance, Zhou et al (2012) and Chou et al (2019) derived the estimator of total factor energy productive efficiency through stochastic frontier production function. This paper follows the theory of Zhou et al (2012).…”
Section: The Assessment Of Energy Efficiencymentioning
confidence: 99%
“…Based on the parametric frontier approach of energy efficiency performance, Zhou et al (2012) and Chou et al (2019) derived the estimator of total factor energy productive efficiency through stochastic frontier production function. This paper follows the theory of Zhou et al (2012).…”
Section: The Assessment Of Energy Efficiencymentioning
confidence: 99%
“…Most studies in the literature examine the influence of CO 2 emissions, inequality, foreign direct investment, and democracy on green technology [10,15,[68][69][70][71][72][73][74][75][76]. Our study extends the analysis into the effects of technological change, environmental policy, political factors, and economic performance on green technology diffusion in a large panel of world economies.…”
Section: Dynamic Panel Data Modelmentioning
confidence: 97%
“…The present study found that the number of studies focusing on new energy policy increases over time. However, most studies focus on the relationship between new energy and low-carbon development (Xu et al, 2019;Chou et al, 2020;Su et al, 2022). Few studies focused on Chinese people's new energy usage behavior (NEUB) and not many studies discussed the impacts on Chinese NEUB by its cognitions of energy-related environmental accidents (CEREA) and people's cognitions of new energy policies (CNEP).…”
Section: Introductionmentioning
confidence: 99%